Lone fatherhood, the deficit of motherly love and institutional discrimination - Šori, Iztok (Teorija in praksa, 2019)
The article critically reflects on the idea of motherly love found in the works of Fromm, Parsons and Bales and empirically examines how lone fathers understand this idea and how it is embedded in the actions of public institutions. Evidence from interviews show that lone fathers perceive motherly love as the only deficit in their care for their children. While through their day-to-day care they intentionally or unintentionally deconstruct gender norms and the boundaries of masculinity, they simultaneously restore them at the level of a less tangible emotional experience. The idea of motherly love being reproduced on the institutional level leads to discrimination against (lone) fathers and the marginalisation of atypical masculinities.
Keywords: Archetype (Psychology); Arhetip (psihologija); Enostarševske družine; Fatherhood; Masculinity; materinska ljubezen; Moškost; Očetovstvo; Single-parent families